Comparative analysis of the specifics of a compliment in Chinese, English and Kazakh speech culture - Кенжебаева, А. А.; Мұқатай, К. (Journal of Oriental Studies, 2017)
The article considers a compliment as a speech act in terms of its object and purpose, depending on the gender of the Chinese, English and Kazakh lingvoculture also considered a compliment design principles, the principles of its formality, used language means.